From epistemic injustice to public knowledge: Peer research and the sociological imagination - Neve Abgeller; Paulina Ramirez; Tony Dobbins (Critical Sociology, 2026)
This paper examines peer research as a sociological practice through which marginalised experience becomes public knowledge. Drawing on a reflexive study of a participatory project in a socioeconomically deprived community in the United Kingdom, it brings the sociological imagination into dialogue with epistemic injustice. The analysis identifies three forms of sociological emancipatory work performed by peer researchers: widening visibility by reaching residents absent from formal consultation; producing intelligibility by translating institutional language into socially reachable forms; and enabling legitimacy by carrying community knowledge into organisational and public spaces. The paper argues that peer research can renew emancipatory sociological imagination by connecting private troubles to public issues from within communities themselves. Yet it also exposes the institutional filters through which participatory knowledge must pass. Peer research therefore expands sociology’s epistemic reach while revealing the uneven conditions under which marginalised knowledge becomes authorised, circulated, and heard.